Frontiers of the Roman Empire = Grenzen des Römischen Reiches = Frontières de l'Empire Romain - Breeze, David J. (Archaeopress Archaeology, 2022)
This text illustrates the historical and archaeological significance of the Upper Germanic Limes and provides an up-to-date overview of its manifold features in the field.